THEORETICAL PRINCIPLES OF SUPPLY CHAIN MANAGEMENT AND EVALUATION OF ITS EFFICIENCY - Кулик, Анна; Самойленко, Антонина (SWorldJournal, 2021)
The work is devoted to the disclosure of the content of the concept of "supply chain management", its application and evaluation of efficiency. The main approaches to this concept are systematized: classical and reference models. Supply Chain Planning (SC